2006
DOI: 10.1016/j.antiviral.2006.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of measles virus and subacute sclerosing panencephalitis virus by RNA interference

Abstract: Subacute sclerosing panencephalitis (SSPE) is a rare, but fatal outcome of measles virus (MeV) infection. SSPE develops after prolonged persistence of mutated MeV called SSPE virus. Although a combination therapy using interferon and inosiplex or ribavirin appears to prolong survival time to some extent, there is currently no effective treatment to completely cure SSPE and a new treatment strategy is greatly needed. In this study, we adopted RNA interference (RNAi) strategy and examined whether small interferi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…In this context, the DNA polymerase or IVa2 genes could be of interest, as their knockdown RNAi proved more effective than that of E1A (37,38). Similarly, aptazyme regulation of the measles virus P or L polymerase genes or of the nucleocapsid N gene may facilitate conditional virus replication, as indicated by RNAi studies (39,40). Finally, the pace of shutting down established virus infections can most certainly be accelerated considerably by combined control of several viral genes blocking viral infections simultaneously at different stages of the virus replication cycle.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the DNA polymerase or IVa2 genes could be of interest, as their knockdown RNAi proved more effective than that of E1A (37,38). Similarly, aptazyme regulation of the measles virus P or L polymerase genes or of the nucleocapsid N gene may facilitate conditional virus replication, as indicated by RNAi studies (39,40). Finally, the pace of shutting down established virus infections can most certainly be accelerated considerably by combined control of several viral genes blocking viral infections simultaneously at different stages of the virus replication cycle.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that siRNAs targeted against the L mRNA of the MV genome (MV-L2, -L4 and -L5) efficiently inhibited replication of both MV and SSPE virus (26). We generated three strains of rAd-siRNA each expressing either one of the three different siR- NAs.…”
Section: Generation Of Rad-sirnamentioning
confidence: 99%
“…Assessment of inhibitory effects of rAd-siRNA on SSPE-Kobe-1 virus replication was performed as reported previously with some modifications (26). In brief, 6 hr after cell seeding, SSPE virus-infected or uninfected Vero/SLAM cells were inoculated with rAdsiRNA at indicated m.o.i.…”
Section: Cells and Mv/sspe Virus Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Small interfering RNAs (siRNAs) have also been described to be active against MV (20,29,32), including an MV isolate from an SSPE patient (SSPE-Kobe-1) (28). In the latter approach, the authors generated recombi-nant adenoviruses (rAdV) expressing siRNA against MV L mRNA and assessed them in freshly infected Vero/SLAM cells.…”
mentioning
confidence: 99%